"An Honest But Fearless Fighter": The Adversarial Ideal of Public Defenders in 1930s and 1940s Los Angeles. (8th August 2018) - Mayeux, Sara
Abstract : Early one Sunday in 1948, Frederic Vercoe set out from his home in San Marino, California, for a speaking engagement in downtown Los Angeles. Perhaps he took the Arroyo Seco Parkway, which had opened for drivers 8 years before, linking the city more tightly with its "vast agglomerate of suburbs." Although the roads may have changed, Vercoe had been making some version of this commute for decades. He had recently retired after a long career with the Los Angeles County Public Defender—13 years as a deputy, followed by 19 years as head of the office—and now maintained a small private law practice downtown. Many mornings, Vercoe would have had business at the Hall of Justice, the ten-story box of "gray California granite" that housed the jails and courtrooms. On this particular morning, he was headed instead to Clifton's Cafeteria at Seventh Street and Broadway. Perhaps, as he drove the dozen miles west into the city, he admired the "geraniums, cosmos, sweet peas, asters and marigolds" that lined the "gardens, parkways, and driveways, " or perhaps he was used to the foliage by now. Vercoe had lived in California for more than 30 years, making him, by West Coast standards, a real "old-timer."